Pelatihan dan Implementasi Sistem Verifikasi Ijazah Digital Berbasis n8n dan Filament di SMKN 1 Kabupaten Tangerang - Asri, Jefry Sunupurwa; Aryani, Diah; Fannya, Puteri; Arfian, Muhamad Hadi; Widyawan, Tri Ismardiko; Ramadhan, Iksan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
This community service activity was conducted to address the problem of diploma verification at SMKN 1 Kabupaten Tangerang, which is still carried out manually, requiring considerable time and posing risks of recording errors and document loss. This activity aims to develop and implement a digital-based diploma verification system to improve efficiency, accuracy, and the quality of administrative services. The system utilizes Laravel Filament as the administrative interface, n8n for workflow automation, MySQL as the database, and Optical Character Recognition (OCR) technology to automatically extract information from diploma documents. The implementation results show a significant performance improvement, where verification time decreased by more than 90%, from 10–15 minutes to less than one minute per document. In addition, data accuracy increased from approximately 85% to 98%, and document retrieval speed improved by more than 80%. Based on user satisfaction questionnaire results, 100% of respondents stated that the system is easy to use and helps accelerate administrative tasks. Therefore, the developed system is proven to be effective in supporting the digital transformation of academic document management in the school environment.